Konsensus Dokter Umum Mengenai Materi Inti Anatomi Sistem Reproduksi Wanita Untuk Mahasiswa Kedokteran - INTAN PRATIWI; YUNIA HASTAMI; NANANG WIYONO; SITI MUNAWAROH (Faculty of Medicine Universitas Sebelas Maret, 2018)
Introduction: The anatomy of the female reproductive system is one of the basic sciences of medical clinical practice needed by general practitioners. Until now there has been no standardization regarding anatomical material of the female reproductive system that medical students need to know. Meanwhile, the medical curriculum has undergone many changes that have impacted on reduced learning time resulting in a reduction in anatomical material given to students. This causes the different emphasis on anatomical material given to be different for each medical institution. This study aims to compile the subject matter of the anatomy of the female reproductive system in order to facilitate anatomical learning for medical students. Methods: This research is a qualitative research with Delphi method two rounds. The subjects were general practitioners from 9 institutions in Indonesia selected through purposive sampling as many as 20 people. The initial Delphi questionnaire was compiled based on three anatomical textbooks, one anatomic terminology, and one study on the anatomical core material. Delphi round I panel is asked to choose material that are important and can add material if it doesn't already exist. Delphi round II panel was asked to rank 1-4 in each material. Researchers set a consensus level of 53%.Results: The results of Delphi round I obtained 176 materials from a total of 178 materials and no additional material was obtained. Delphi round II obtained 84 (47.72%) core anatomical materials from 176 material.Conclusion: General practitioners consensus of core materials of female reproductive system anatomy is 84 materials.